Nostalgia and Culture: The Relationship Between Indicators of Acculturation and Nostalgia - Borsali Awicha Amina; Benhabib Abderrezak (Journal of Marketing and Consumer Behaviour in Emerging Markets)
In this article we test the relationship between indicators of acculturation (language, media, selfidentification, religion, food and clothing) and nostalgia. It checks empirically, on a sample of 201, the existence of a significant effect between our independent variables and our dependent variable. The results of analysis of variance, One-Way Anova, reveal that the home language, the food of home country, the media, self-identification with the origin country and the religion of the origin country have a signifi cant impact on nostalgia. This article contributes to new theoretical elements in the field of nostalgia and culture as a complement of several previous studies. The managerial contributions of this study focus on positioning of nostalgic brands and developing marketing strategies for this kind of products.